"We own the illness”: a qualitative study of networks in two communities with mixed ethnicity in Northern Norway - Larsen, Anette Iren Langås; Salamonsen, Anita; Kristoffersen, Agnete Egilsdatter; Hamran, Torunn; Evjen, Bjørg; Stub, Trine (International Journal of Circumpolar Health, 2018)
Source at https://doi.org/10.1080/22423982.2018.1438572 . Background: When people in Northern Norway get ill, they often use traditional medicine. The global aim of this study was to examine the extended family networks’ function and responsibility in cases of illness in the family, in two Northern Norwegian communities with a population of mixed ethnicity. Methods: Semi-structured individual interviews with 13 participants and 4 focus group interviews with total 11 participants were conducted. The text data was transcribed verbatim and analysed based on the criteria for content analysis. Results: The participants grew up in areas where it was common to seek help from traditional healers. They were organized in networks and shared responsibility for the patient and they provided practical help and support for the family. According to the networks, health-care personnel should make room for the entire network to visit the patient in severe and life-threatening situations. Conclusion: Traditional networks are an extra resource for people in these communities. The networks seem to be essential in handling and disseminating hope and manageability on an individual as well as a collective level. Health personnel working in communities with mixed ethnicity should have thorough knowledge of the mixed culture, including the importance of traditional network to the patients.